Peningkatan Kualitas Dosen Melalui Pelatihan Pengabdian Masyarakat pada Universitas Abulyatama Aceh - Ilham; Ema Dauyah Ema Dauyah; Samsuar; M.Nasir Ismail (STAI Nusantara Kota Banda Aceh, 2025)
Community service is an integral part of the Tri Dharma Perguruan Tinggi (Three Pillars of Higher Education) that must be carried out by every lecturer. However, the quality of community service is greatly influenced by the capacity and competence of lecturers as implementers. This article discusses efforts to improve the quality of lecturers at Abulyatama University Aceh through a systematically designed community service training programme. The method used in this study is a qualitative descriptive approach through document analysis, observation, and in-depth interviews with faculty members participating in the training. The results of the study indicate that the training effectively improved faculty members' understanding of community service methodology, proposal development, as well as the implementation and evaluation of programs. This article recommends regular training, a mentoring system, and the integration of community service with research as strategies for sustainable quality improvement.